TINGKAT PENGETAHUAN, SIKAP DAN PERILAKU TENTANG GLAUKOMA PADA TENAGA KESEHATAN DI PUSKESMAS SE-KOTA MAKASSAR, PROVINSI SULAWESI SELATAN, INDONESIA - Andi Tenrisanna Devi Indira; Ariyanie Nurtania; Rihlah Thahirah Al-Hikmah (RS Mata Makassar: Journal of Ophthalmology, 2024)
ABSTRACT Introduction: Glaucoma is the leading cause of irreversible blindness worldwide. The prevalence of glaucoma is estimated at 111.8 million people will suffer from glaucoma in 2040, so that through good knowledge, attitudes, and behavior of health workers, it can support the control of the severity of glaucoma. Purpose: To assess awareness and knowledge about glaucoma, attitude and behavior to glaucoma screening in Health center, Makassar city, South Sulawesi, Indonesia. Methods: Quantitative with cross sectional descriptive research design. Through filling iut questionnaires on 107 Health workers at Makkassar health city center on September 11 -12. In this research there are theree variables that are assessed, namely knowledge, attitude, and behavior. Result: Health workers As many as 52 respondents had a good level of knowledge, 55 respondents had a sufficient level of knowledge, and no respondents had a poor level of knowledge. Attitudes towards glaucoma were obtained 86 respondents (80.4%) conducted visual acuity tests on patients who complained of impaired vision, 76 respondents (71%) conducted visual field tests on patients suspected of glaucoma, 71 respondents (66.4%) conducted eyeball palpation examinations on patients suspected of glaucoma, and as many as 98 respondents (91.6%) behaved positively as indicated by referring patients with glaucoma to hospitals that have eye specialists. Conclusion: Awareness and level of knowledge about glaucoma among health workers in health centers are good. This condition can help in suppressing the occurrence of permanent blindness due to glaucoma. Efforts to prevent blindness due to glaucoma can be done by increasing the knowledge, attitudes, and behavior of health workers so that glaucoma can be detected early. Keywords: glaucoma, awareness, knowledge, attitude, behavior, glaucoma screening